Plant protein degradation affects transcription of genes associated with bacterium-induced basal resistance - Zsiros, László Róbert (Acta Biologica Szegediensis, 2008)
Basal reistance (BR), being the first line of all active defense forms in plants, is induced rapidly after a microbial invasion of the plant tissues. There is an endeavor to discover the processes taking place in the plant cell during BR. It is already known that upon a bacterial attack certain plant genes show transcriptional changes. Our present work is an excerpt of studies made on the effect of protein degradation systems on the expression of BR associated genes. Tobacco plants were infected with a non-HR inducing bacterium (Pseudomonas syringaepv. syringes hrcC) to trigger BR. Parallel treatments were carried out with protein degradation inhibitors. Alterations in gene expression were measured with real-time PCR and microarray methods. Our results support that protein degradation may affect the BR-related genes through the decomposition of signalling proteins and/or transcription factors that play role in the development of defense responses.